2018
DOI: 10.1111/bjso.12256
|View full text |Cite
|
Sign up to set email alerts
|

Are people more prejudiced towards groups that are perceived as coherent? A meta‐analysis of the relationship between out‐group entitativity and prejudice

Abstract: A meta-analysis was conducted to examine the relationship between out-group entitativity and prejudice. A quantitative analysis of 85 effect sizes from 33 independent samples showed a significant positive relationship between entitativity and prejudice (Fisher's z = .414, 95% CI [0.272, 0.557], p < .0001). Three possible moderators of the relationship between entitativity and prejudice were tested: conceptualization of the entitativity (essence-based entitativity scale, agency-based entitativity scale, common … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 74 publications
4
20
1
Order By: Relevance
“…It is generally assumed that these tendencies would explain the development of positive stereotypes about the ingroup, negative stereotypes about the outgroup, and discrimination among social groups (Abrams & Hogg, ; Scandroglio, López Martínez, & San José Sebastián, ; Tajfel & Turner, /2001). Importantly for our current work, it has been found that negative attitudes towards the outgroup depend on it being perceived as a homogeneous entity (i.e., entitativity; Agadullina & Lovakov, ), which is consistent with the view that stereotypes are conceptual (Macrae & Bodenhausen, ), and not merely attitudinal phenomena.…”
Section: A Standard Account Of Stereotypessupporting
confidence: 90%
“…It is generally assumed that these tendencies would explain the development of positive stereotypes about the ingroup, negative stereotypes about the outgroup, and discrimination among social groups (Abrams & Hogg, ; Scandroglio, López Martínez, & San José Sebastián, ; Tajfel & Turner, /2001). Importantly for our current work, it has been found that negative attitudes towards the outgroup depend on it being perceived as a homogeneous entity (i.e., entitativity; Agadullina & Lovakov, ), which is consistent with the view that stereotypes are conceptual (Macrae & Bodenhausen, ), and not merely attitudinal phenomena.…”
Section: A Standard Account Of Stereotypessupporting
confidence: 90%
“…To account for statistical dependencies, we further conducted PET and PEESE meta-regression with RVE using the R package robumeta (Fisher et al, 2016). “Because PET underestimates nonzero effects and PEESE overestimates null effects” (Agadullina & Lovakov, 2018, p. 712), a two-step conditional PET-PEESE procedure is recommended: If PET finds a significant effect, then the PEESE estimate is preferred; if PET does not find a significant effect, then the PET estimate is preferred (Agadullina & Lovakov, 2018; Stanley & Doucouliagos, 2014). Analyses revealed that both PET, b = 3.98, SE = 1.86, t (5.32) = 2.14, p = .08, and PEESE, b = 25.64, SE = 15.64, t (1.69) = 1.64, p = .26, were not significant.…”
Section: Resultsmentioning
confidence: 99%
“…Because the studies used different analytical strategies, we converted all effect sizes to the same metric, Pearson’s r , and applied Fisher’s z transformation. When r was unavailable but the standardized regression coefficient (β) was available, we followed the commonly used β-to- r imputation formula: r = β + .05λ, where λ equals 1 when β is nonnegative, and λ equals 0 when β is negative (Peterson & Brown, 2005; for a recent meta-analysis example, see Agadullina & Lovakov, 2018, p. 711). For comparison purposes, we present effect sizes that account for population as a key covariate (e.g., crime rate = number of crimes divided by population).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, our results provide new evidence of how entitativity can exacerbate intergroup conflict. Whereas much work shows that viewing a group as entitative can stoke stereotyping and prejudice (Agadullina & Lovakov, 2018;Brewer & Harasty, 1996;Er-rafiy & Brauer, 2013;Spencer-Rodgers, Hamilton, & Sherman, 2007), the present work shows it can license individual members of that group to express prejudice against others.…”
Section: Theoretical Contributionsmentioning
confidence: 50%